The Process of Reforming the System of State Administration and Administrative Reform in Uzbekistan - AKHMEDSHAEVA, Mauvlyuda Akhatovna; NAZHIMOV, Makhmud Kamaladiinovich; MUKHAMEDOV, Khajdarali Melievich; ABDURASHIDOVNA, Mukhitdinova Firuza (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020DO - 10.14505/jarle.v11.2(48).01, 2020)
The research considers the processes of formation of the latest legislation on administrative responsibility in the Republic of Uzbekistan its relevance and problems that should receive proper scientific evaluation. The author considers and analyzes the reform in the field of a new model of administrative-tort legislation proceeding from the paradigm of priority jurisdictional protection of human rights and freedoms.